Adolescents With Eating Disorders in Pediatric Practice - The European Academy of Paediatrics Recommendations - Agnieszka Rynkiewicz; Agnieszka Rynkiewicz; Łukasz Dembiński; Łukasz Dembiński; Berthold Koletzko; Berthold Koletzko; Pierre-André Michaud; Pierre-André Michaud; Adamos Hadjipanayis; Adamos Hadjipanayis; Adamos Hadjipanayis; Zachi Grossman; et al. (Frontiers Media S.A., 2022)
In the face of the growing number of adolescents suffering from eating disorders (EDs) and access to psychiatric care limited by the epidemiological and demographic situation, the primary care pediatrician's role in diagnosing and treating EDs is growing. The European Academy of Paediatrics (EAP) decided to summarize knowledge about EDs and formulate recommendations to support European pediatricians and improve care for adolescents with EDs.